2022
DOI: 10.51474/jer.v12i1.595
|View full text |Cite
|
Sign up to set email alerts
|

Inspirational Leadership Among Teachers: An Explanatory Sequential Mixed-Methods Study in the School Setting of Nepal

Abstract: Inspirational Leadership (IL) is pivotal in the spaces of educational leadership to inspire and motivate teachers to achieve organisational goals. Concerning it, this study intends to explore the existence of inspirational leadership among teachers of Bagmati Province. For this purpose, this study employed explanatory sequential mixed method design, a cross-sectional survey in Quan strands and narrative inquiry in Qual strands. The data in the Quan and Qual strands were gathered via survey questionnaires from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This is aligned to finding of Glaz and Liang (2009), who further stated that such incorporation (poetry as well) to mathematics results in enhancement of both learning and proficiency of mathematical concepts, and also helps in reducing math-anxiety. In relation to it (and to storytelling as well: illustrated in story 1 of episode 3), Shrestha et al (2022) also stated about the significance of arts-based pedagogy, which can assist both teachers and students, in terms of promoting self-motivation, creativity, imagination, and critical thinking. Thereby, I found that 42 days training as a huge asset for me during my two years of Fellowship journey.…”
Section: (Everyone Seems Happy and It Is Delightful To See Their Exci...mentioning
confidence: 99%
“…This is aligned to finding of Glaz and Liang (2009), who further stated that such incorporation (poetry as well) to mathematics results in enhancement of both learning and proficiency of mathematical concepts, and also helps in reducing math-anxiety. In relation to it (and to storytelling as well: illustrated in story 1 of episode 3), Shrestha et al (2022) also stated about the significance of arts-based pedagogy, which can assist both teachers and students, in terms of promoting self-motivation, creativity, imagination, and critical thinking. Thereby, I found that 42 days training as a huge asset for me during my two years of Fellowship journey.…”
Section: (Everyone Seems Happy and It Is Delightful To See Their Exci...mentioning
confidence: 99%
“…The influence of inspirational motivation on teachers' job satisfaction in public secondary schools This section focuses on reviewed empirical studies related to the contribution of inspirational motivation to teachers' job satisfaction in public secondary schools. A study conducted by Shrestha (2022) Inspirational Leadership among Teachers: an Explanatory Sequential Mixed Methods Study in the School Setting of Nepal Asia. For this purpose, the study employed explanatory sequential mixed method design, a cross-sectional survey in Quantitative strands and narrative inquiry in Qualitative strands.…”
Section: Literature Review and Knowledge Gapmentioning
confidence: 99%
“…The NCSL also conducts research and advocates for policies that support the development of effective school leadership in India (Ministry of Education, 2021). According to various studies, the School Leadership Development Program (SLDP) in Nepal has had a positive impact on the quality of education in the country (Nepal Government, 2015;Shrestha, 2017;Subedi, 2015;UNICEF, 2018). The program has helped to develop critical leadership skills such as communication, conflict resolution, and decision-making, resulting in better management of schools, improved teacher performance, and better learning outcomes for students (Shrestha, 2017;Subedi, 2015).…”
Section: C) National Centre For School Leadership (Ncsl) In Indiamentioning
confidence: 99%
“…According to various studies, the School Leadership Development Program (SLDP) in Nepal has had a positive impact on the quality of education in the country (Nepal Government, 2015;Shrestha, 2017;Subedi, 2015;UNICEF, 2018). The program has helped to develop critical leadership skills such as communication, conflict resolution, and decision-making, resulting in better management of schools, improved teacher performance, and better learning outcomes for students (Shrestha, 2017;Subedi, 2015). Moreover, the program has also emphasized the importance of collaboration among stakeholders, including parents, teachers, and community members, resulting in better school performance and greater accountability (Nepal Government, 2015;UNICEF, 2018).…”
Section: C) National Centre For School Leadership (Ncsl) In Indiamentioning
confidence: 99%
See 1 more Smart Citation